Militant democracy the limits of democratic tolerance - Rijpkema, Bastiaan 1987- (Routledge studies in extremism and democracy, 2018)
This book aims to present a comprehensive theory of militant democracy and to answer questions such as: How can a democracy protect itself against its own downfall? And when is intervention against antidemocrats justified? Against the backdrop of historical and current examples, this book examines a variety of theories from philosophers and legal scholars such as Karl Loewenstein, Karl Popper and Carl Schmitt as well as contemporary alternatives. It compares their interpretations of democracy and militant democracy, discusses how helpful these references are, and introduces two largely forgotten theorists to the militant democracy debate: George van den Bergh and Milan Markovitch. Militant Democracy then sets out to build a novel theory of democratic self-defence on the basis of democracy's capacity for self-correction. In doing so, it addresses the more classic and current criticisms of the concept, while paying specific attention to the position of the judge, the legal design and effectiveness of party bans, and the national and supranational procedural safeguards that can safeguard the careful application of militant democracy instruments. Militant Democracy seamlessly combines political philosophy, political science and constitutional law to offer a new perspective on democratic self-defence. This book is essential reading for scholars and students of political theory, jurisprudence, democracy, extremism and the history of ideas